(untitled) (Mustansiria Dental Journal, 2018)
Background: Streptococcus mutans is capable of demineralizing enamel by producing an acidic environment. Therefore, control of the bacterial biofilm on teeth is essential for the maintenance of oral health. The NBF jel with propolis ingredient that manufactured by nano-biofusion technology which has an antimicrobial activity as it is confirmed by many previous studies expected to induce more antimicrobial effect than traditional product and lastly overcome the bacterial biofilm and prevent the carries and others oral medical problems. Aim of study : To evaluate the antibacterial action of NBF jel on Strep. mutans isolated from orthodontic appliance. Material and method: Saliva samples were collected from 36 patients wearing appliance for different duration. Strep. mutans was isolated ,purified and diagnosis , then prepared two extracts from NBF jel (aqouse and alcoholic) in different concentration , chlorhexidine 2%(control) were added to isolated bacteria. After incubation for 48 hours; the inhibition zone of antibacterial activity of NBF was measured and colony count of bacteria was counted. Results: The two types of extracts have had antimicrobial activity but the alcoholic extract was induced more action than aqouse one as well as their effect was less than the chlorhexidine 2%(control). The inhibition zone was increased with increasing the concentration of both extracts but the responsiveness was reduced with increased the period of using the appliance. The reduction in colony counts of strep. Conclusion : NBF jel had antimicrobial activity against Strep. mutans isolated from appliance and this activity indirectly correlated with duration of wearing.